Antenna Design for Ultra-Wideband System Using a Fractal H-Shaped Structure for Enhanced Filtering and Narrowband Operation - Mohsin, Noor K.; Naji, Dhirgham K. (Al-Nahrain Journal for Engineering Sciences, 2025)
In this work, for ultra-wideband (UWB) applications, a passive filter antenna with edge chamfering is investigated in this paper. The performance of an optimized UWB antenna design that achieves an advanced fractional impedance bandwidth of 102% is confirmed by simulation and experimentation. The performance of the antenna is improved by integrating a lowpass filter (LPF) into the fed line, which suppresses high-frequency radiation with a central frequency of 3.5 GHz (WiMAX), the UWB antenna has been transformed into a narrowband antenna, offering a 43.7% fractional bandwidth that spans the frequency range from 2.7 GHz to 3.9 GHz. A stepped impedance transmission line and an extended fractal H-shaped structure integrated in the microstrip feedline make up the filtering network. Using CST Microwave Studio (CST MWS), key performance parameters such as the radiation patterns, efficiency, gain, and reflection coefficient (S11) were examined. In its prototype, the antenna reduces its size by 5% and is made on a FR4 substrate with a permittivity coefficient of 4.3 and a loss tangent of 0.02. A maximum gain of 1.7 dBi and a peak efficiency of 78% at the center frequency were verified experimentally. The center frequency was verified experimentally. The tiny antenna, which measures 0.30λ₀ × 0.37λ₀ × 0.008λ₀, performs well and is appropriate for UWB applications. The design makes a significant addition to the realm of UWB technology by incorporating elements that improve its ability to adapt.